Surface-Engineered MoO[sub.x]/CN Heterostructures Enable Long-Term SF[sub.6] Photodegradation via Suppressed Fluoridation - Zhou, Wenhui; Dong, Boxu; Si, Ziqi; Xu, Yushuai; He, Xinhua; Zhan, Ziyi; Zhang, Yaru; Song, Chaoyu; Lv, Zhuoqian; Zai, Jiantao; Qian, Xuefeng (Molecules (Basel, Switzerland), 2025)
Sulfur hexafluoride (SF[sub.6]), the strongest greenhouse gas, has great challenges in degradation because of its stable structure, posing significant environmental concerns. Photocatalysis offers an environmentally friendly, low-energy solution, but the fluoride deposition on catalysts reduces their activity, thus limiting their large-scale application. To prevent catalyst fluoride poisoning, we report a thin-layer graphitic carbon nitride (CN) material loaded with MoO[sub.x] (CNM) that resists fluoride deposition for long-term SF[sub.6] degradation. By combining molecular structure design and nanostructure regulation, we construct a photocatalyst with enhanced charge carrier mobility and reduced transport distances. We find that the CNM exhibits a high specific surface area, increased contact between reactants and active sites, and efficient electron–hole separation due to the Mo-N bonds, achieving an SF[sub.6] degradation efficiency of 1.73 mmol/g after one day due to the prolonged catalytic durability of the catalyst, which is eight times higher than pristine g-C[sub.3]N[sub.4] (0.21 mmol/g). We demonstrate the potential of CNMs for low-energy, high-efficiency SF[sub.6] degradation, offering a new approach to mitigate the environmental impact of this potent greenhouse gas. We envision that this study will inspire further research into advanced photocatalytic materials for environmental remediation, contributing to global efforts in combating climate change.